Construction of keratin 5-IRES-eGFP knockin hESCs cell line - Wen ZHENG; Yadan ZHONG; Xuan WANG; Huiting LIU; Bin YANG; Jun LIU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To establish keratin 5-IRES-eGFP knockin hESCs cell line by using CRISPR/Cas9 technique, which could provide a cell model for the study of skin diseases with abnormal basal keratinocytes in the epidermis. Methods The sgRNA plasmid and target Donor plasmid targeting gene keratin 5 were constructed, and IRES-eGFP was knocked-in the target gene keratin 5 via CRISPR/Cas9 technique in hESCs, then the cell line were differentiated to basal keratinocytes with green fluorescent protein (GFP). Results PCR and Sanger sequencing results showed that IRES-eGFP was successfully integrated into the upstream of keratin 5 in hESCs cell line. The cell morphology was consistent with that of keratinocytes cell line HaCaT after differentiation and culture and the ES-KC cell line derived from hESCs differentiation was confirmed to express GFP and Keratin 5 stably by immunofluorescence staining. Conclusion Keratin 5-IRES-eGFP knockin hESCs cell lines are successfully constructed and are differentiated into basal keratinocytes labeled with GFP, which laid a foundation for subsequent experiments.